Kinetic bottlenecks to chemical exchange rates for deep-sea animals II: Carbon dioxide - Hofmann, Andreas F.; Peltzer, Edward T.; Brewer, Peter G. (Copernicus Publications, 2012)
Increased ocean acidification from fossil fuel CO2 invasion, from temperature-driven changes in respiration, and from possible leakage from sub-seabed geologic CO2 disposal has aroused concern over the impacts of elevated CO2 concentrations on marine life. 5 Discussion of these impacts has so far focused only on changes in the oceanic bulk fluid properties as the critical variable and with a major focus on carbonate shell dissolution. Here we describe the rate problem for animals that must export CO2 at about the same rate at which O2 is consumed. We analyze the basic properties controlling CO2 export within the diffusive boundary layer around marine animals in an ocean changing in temperature (T) and CO2 concentration in order to compare the challenges posed by O2 uptake under stress with the equivalent problem of CO2 expulsion. The problem is more complex than that for a non-reactive gas since, as with gas exchange of CO2 at the air-sea interface, the influence of the ensemble of reactions within the CO2-HCO−CO2−acid-base system needs to be considered. These reactions significantly facilitate CO2 efflux compared to O2 intake at equal temperature, pressure and flow rate under typical oceanic concentrations.The effect of these reactions can be described by an enhancement factor. For organisms, this means mechanically increasing flow over their surface to thin the boundary layer as is required to alleviate O2 stress seems not necessary to facilitate CO2 efflux. Nev20 ertheless the elevated pCO2 cost most likely is non-zero. Regionally as with O2 the combination of T , P , and pH/pCO2 creates a zone of maximum CO2 stress at around 1000m depth. But the net result is that, for the problem of gas exchange with the bulk ocean, the combination of an increasing T combined with declining O2 poses a greater challenge to marine life than does increasing CO2. The relationships developed here allow a more accurate prediction of the impacts on marine life from the combined effects of changing T , O2, and CO2 than can be ...